Mechanical Properties of Antarctic Sea Ice: Mechanische Eigenschaften von antarktischem Meereis - Paul, Felix (2023)
Sea ice in the Antarctic is crucial for the global climate. Its seasonal variations are of significant importance for Antarctic bio-habitat, primary production, heat, and carbon dioxide uptake of the ocean. However, the annual sea ice cycle, with extensions and declines in the Southern Ocean, is not completely understood yet. One reason for this is the poor understanding of the mechanical properties of Antarctic sea ice, which differ from the ones of the Arctic sea ice. To overcome the gap, the rheological properties of frazil ice and the compressive strength of pancake ice as well as consolidated sea ice were measured during three SCALE cruises in the marginal ice zone of the Antarctic. Frazil ice, consisting of small ice crystals floating in water, is the first ice forming in the annual freezing cycle of the Antarctic. It later develops into consolidated pancake ice floes and afterward into a consolidated sea ice cover. The rheological properties of frazil ice are determined with the help of a vane rheometer immediately after sampling the ice from the Southern Ocean. The flow curve of frazil ice can be separated into three phases: In the beginning (1) the shear stress increase caused by hooking of the crystals, followed by (2) a shear stress decrease caused by detangling of the crystals and ultimately (3) shearing between the crystals in the third phase. Frazil ice shows a shear thinning behavior in the third phase with a flow index of n = 0.5. Sea ice compressive strength is tested with two different hand-driven compression jigs. Tests are performed at –10 °C after a short-time storage with a strain rate in the ductile-to-brittle transition zone, as this yields the highest strength. Compressive strength results are presented depending on porosity, brine volume, and sea ice depth. Sea ice strength is higher in spring than in winter, and Antarctic sea ice is generally weaker than its Arctic counterpart. Das Meereis in der Antarktis spielt eine wichtige Rolle für das globale Klima. Die jahreszeitlichen ...